Storytelling Services with Cognitive Restructuring Methods There are Traumatized Bullying Teens Who Report at UPTD PPA Makassar City - Dian Novita Siswanti; Gina Wardayani; Nurul Khotimah; Islamiyah; Isabella Juli Tresnadi; Ezza Arianty (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find out and help clients regarding the problems they face and find out what potential clients can develop from bullying problems. Bullying behavior is no stranger to schools, especially teenagers. Teenagers will question who they are, what their roles are, and what they will do for their lives so that they will conduct many experiments in their lives. Not infrequently, this is what then causes a variety of deviant behavior in adolescents, one of which is bullying. The subjects in this study were 5 students of SMP Negeri 1 Makassar City who were involved in a viral video of bullying cases. Researchers used qualitative research methods with a descriptive approach. The reason the researcher uses a descriptive qualitative research method is because it makes it easier to collect data in accordance with the chronology that is told in a systematic, factual and actual manner.